Optimalisasi Pemanfaatan Android pada Sistem Peringatan dan Monitoring Keamanan Perlintasan Kereta Api - Masril, Mardhiah; Retno Devita; Hasri Awal; Lusi Andriani (LPPM-ITEBA, 2024)
Railroad crossing security on highways is an important issue for road user safety. The current security system still has limitations, such as a lack of timely response and negligence of crossing guards, resulting in a high number of accidents at railroad crossings, which often claim lives. The high rate of accidents that occur today causes safety to be one of the most important things. Therefore, it is necessary to apply sophisticated technology to minimize the risk of accidents. The utilization of computer technology in the railway crossing security system can be an optimal solution. The system will work by using sensors that are able to detect the arrival of trains and send information about the state of the crossing to the crossing guards in real time. Thus, the crossing guards can take appropriate and quick action if there is a malfunction in the system. By integrating advanced technology, it is hoped that accidents at railway crossings can be minimized and the safety of road users can be guaranteed.